Polymer carrier selection for creation of diosmin solid dispersion system by hot melt extrusion - A. A. Danilova; E. V. Vishnyakov; E. S. Surbeeva; K. A. Gusev; D. N. Maimistov; E. V. Flisyuk (Разработка и регистрация лекарственных средств, 2023)
Introduction. The extremely unfavorable physical, chemical and functional properties of diosmin, a component of a number of popular phleboprotective drugs, cause an increased therapeutic dosage of the active pharmaceutical ingredient (API) in the dosage form and complicate the manufacturing process. In order to improve the characteristics of API, a technology of solid dispersion systems (SDS) creation by hot melt extrusion (HME) has been proposed. Particular importance in the context of current approach is attached to the selection of an effective polymer matrix.Aim. The selection and justification of using a polymer carrier from the polyvinylpyrrolidone group for creating diosmin solid dispersions by hot melt extrusion.Materials and methods. Object of study: diosmin (powder micronized substance, Chengdu Runde Pharmaceutical Co., Ltd., China). As candidates for the development of solid dispersions with a model ratio of API to carrier of 1 : 99, two related hydrophilic polymers were selected: a copolymer of polyvinylpyrrolidone with vinyl acetate in a ratio of 60 : 40 (PVPVA) – VIVAPHARM® PVP/VA 64 (JRS PHARMA GmbH & Co. KG, Germany), and polyvinylpyrrolidone brand Kollidon® K17 PF (BASF, USA). The thermal properties of the API and polymer carrier were characterized using synchronous thermal analysis. Diosmin SDS were obtained using a HAAKE™ MiniCTW twin-screw extruder (Thermo Fisher Scientific, Germany). The quantitative content of diosmin in the solid dispersions was determined by HPLC. To assess the effect of the extrusion process on the sample characteristics, the functional properties of API and milled SDS were compared. In particular, the thermal and structural characteristics were studied using differential scanning calorimetry and FTIR spectroscopy, respectively.Results and discussion. Kollidon® K17 is not effective in binary diosmin solid dispersions due to the increased viscosity of the melt, the risk of forming a heterogeneous system, and the potential degradation of the samples' functional properties relative to the pure micronized API. Taking into account the specifics of the extrusion process, as well as the results of the thermal, structural, and functional characteristics analysis of SDS, it was concluded that copolymer of polyvinylpyrrolidone with vinyl acetate is the most effective. This polymer matrix enables more uniform dispersion and fusion with diosmin, along with a tendency towards possible amorphization of the API, and thus – the possibility of solubility properties improvement.Conclusion. The utilization of a copolymer of polyvinylpyrrolidone with vinyl acetate improves the unfavorable characteristics of micronized diosmin, which will eventually eliminate deviations during the manufacturing process of solid dosage forms by reducing the risks of dust formation and mechanical losses, as well as ensuring uniform dosing.